Virtual Screening and Biomolecular Interactions of CviR-Based Quorum Sensing Inhibitors Against Chromobacterium violaceum - Ravichandran, Vinothkannan; Zhong, Lin; Wang, Hailong; Yu, Guangle; Zhang, Youming; Li, Aiying (Frontiers in Cellular and Infection Microbiology, 2018)
The rise of bacterial multi drug resistance becomes a global threat to the mankind. Therefore it is essential to find out alternate strategies to fight against these “super bugs.” Quorum sensing (QS) is a cell-to-cell communication mechanism by which many bacteria regulate their biofilm and virulence factors expression to execute their pathogenesis. Hence, interfering the quorum sensing is an effective alternate strategy against various pathogens. In this study, we aimed to find out potential CviR-mediated quorum sensing inhibitors (QSIs) against Chromobacterium violaceum. Virtual screening from a natural products database, in vitro biofilm and violacein inhibition assays have been performed. Biofilm formation was investigated using confocal microscopy and gene expression studies were carried out using qRT-PCR. Further, to study the biomolecular interaction of QSIs with purified CviR Protein (a LuxR homologue), microscale thermophoresis (MST) analysis was performed. Results suggested that phytochemicals SPL, BN1, BN2, and C7X have potential GScore when compared to cognate ligand and reduced the biofilm formation and violacein production significantly. Especially, 100 μM of BN1 drastically reduced the biofilm formation about 82.61%. qRT-PCR studies revealed that cviI, cviR, vioB, vioC, vioD genes were significantly down regulated by QSIs. MST analysis confirmed the molecular interactions between QSIs and purified CviR protein which cohere with the docking results. Interestingly, we found that BN2 has better interaction with CviR (Kd = 45.07 ±1.90 nm). Overall results suggested that QSIs can potentially interact with CviR and inhibit the QS in a dose dependent manner. Since, LuxR homologs present in more than 100 bacterial species, these QSIs may be developed as broad spectrum anti-infective drugs in future.